Online Handwritten Strokes Recognition using Support Vector Machines: A Statistical Approach for Online Handwritten Devanagari Strokes Recognition (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Handwriting recognition can be viewed in two forms as offline and online handwriting recognition. This study has been done for online handwriting recognition. The present work is a step for online handwriting recognition in Indic scripts. This paper recognizes online handwritten Devanagari strokes using a statistical recognition technique Support Vector Machines. The results have been achieved as 93.27, 89.12 and 99.08 for upper, middle and lower zone Devanagari classes, respectively.